Dinamika Kepribadian Narapidana Kasus Pembunuhan Dengan Antisocial Personality Disorder - Bagus Haria Hadi; Setyani Alfinuha (LPPM Universitas Proklamasi 45, 2022)
Antisocial personality disorder is a disorder that occurs in a person's personality function characterized by irregularities and violations of norms in the environment. This study aims to determine the personality dynamics of someone who has an antisocial personality disorder, especially for prisoner. In addition, researchers also identified the cause of a person experiencing antisocial personality disorder. In this research the method used is case study and qualitative with one participant. Participant is an inmate of a family murder case consisting of husband, wife, and a child. During the research process, researchers conducted observations, interviews, and several psychological tests. The results of this study indicate that behavioural disorders that occur in participants, not formed in a short time but since childhood. There are external and internal factors that affect participants who have these personality disorders. Antisocial personality disorder affects murder cases.